Global burden of reported lower respiratory system fungal infection - Wang, Zheng; Pan, Mengshu; Zhu, Jie (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundThe epidemiological trend of lower respiratory tract fungal infections remains unclear. This study aims to quantify the global burden of these infections from 1990 to 2021 using data from the Global Burden of Disease Study 2021.MethodsData were analyzed at global, regional, and national levels, considering factors such as age, gender, region, and socio-demographic index (SDI). Key indicators included age-standardized disability-adjusted life-year (ASDR) and age-standardized mortality rates (ASMR).ResultsOn a global scale, the burden of lower respiratory fungal infections decreased significantly from 1990 to 2021, with a decline in mortality rates. Regionally, substantial disparities were observed among the 21 geographic super-regions. Nationally, Argentina experienced the greatest increase in ASDR and ASMR, while Finland showed the largest decrease, with average annual percentage changes (AAPC) below -5 for both indicators. Sex-based analysis revealed a notably higher burden in males compared to females. ASDR and ASMR were negatively correlated with SDI in most regions.ConclusionAlthough the global burden of lower respiratory tract fungal infections has decreased, it remains a substantial public health issue, particularly in low-SDI regions. There is an urgent need to implement targeted preventive measures to address this ongoing challenge.